2021
DOI: 10.1093/cvr/cvab200
|View full text |Cite
|
Sign up to set email alerts
|

Progress in cardiac research: from rebooting cardiac regeneration to a complete cell atlas of the heart

Abstract: We review some of the important discoveries and advances made in basic and translational cardiac research in 2020. For example, in the field of myocardial infarction (MI), new aspects of autophagy and the importance of eosinophils were described. Novel approaches such as a glycocalyx mimetic were used to improve cardiac recovery following MI. The strategy of 3D bio-printing was shown to allow the fabrication of a chambered cardiac organoid. The benefit of combining tissue engineering with paracrine therapy to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 94 publications
1
32
0
Order By: Relevance
“…In addition, the reduction of ACE2 will increase ROS generation due to enhanced NADPH activity and reduce mitochondrial homeostasis. A recent study of genome-wide transcriptional alterations induced by SARS-CoV-2 infection in IPSC-CMs had revealed that genes involved in mitochondrial function and energy production were downregulated, indicating that SARS-CoV-2 might promote a shift toward a glycolytic metabolism by suppressing mitochondrial oxidative phosphorylation, which could also favor its replication 68 . Owing to the excessive production of ROS in the heart, a potential anti-oxidative therapy had been suggested to alleviate cardiogenic casualties caused by COVID-19.…”
Section: The Main Mechanism Mediating Cardiac Injurymentioning
confidence: 99%
“…In addition, the reduction of ACE2 will increase ROS generation due to enhanced NADPH activity and reduce mitochondrial homeostasis. A recent study of genome-wide transcriptional alterations induced by SARS-CoV-2 infection in IPSC-CMs had revealed that genes involved in mitochondrial function and energy production were downregulated, indicating that SARS-CoV-2 might promote a shift toward a glycolytic metabolism by suppressing mitochondrial oxidative phosphorylation, which could also favor its replication 68 . Owing to the excessive production of ROS in the heart, a potential anti-oxidative therapy had been suggested to alleviate cardiogenic casualties caused by COVID-19.…”
Section: The Main Mechanism Mediating Cardiac Injurymentioning
confidence: 99%
“…During the worldwide outbreak of COVID-19, the hIPSC-CM-EHT model has contributed to several types of investigations that: 1) mimicked myocardial injuries caused by SARS-CoV-2 infection ( Li et al, 2021 ; Perez-Bermejo et al, 2021 ; Salerno et al, 2021 ; Xie et al, 2022 ); 2) evaluated the safety of different types of vaccines including mRNA and adenovirus vaccines, especially across different ethnic populations with different genomic backgrounds ( Bojkova et al, 2020 ; Lu et al, 2020 ; Davidson et al, 2021 ); and 3) assessed the potential side effects of anti-COVID-19 developed treatments on cardiomyocytes ( Charrez et al, 2021 ; Deguchi et al, 2021 ; Dimai et al, 2021 ). Research involving the hIPSC-CM-EHT model in COVID-19 has rapidly extended the application of hIPSC, making it a more common conceptual and powerful investigative tool.…”
Section: Application Of the Human-induced Pluripotent Stem Cells-deri...mentioning
confidence: 99%
“…Autophagy also plays a key role in other diseases including obesity and diabetes, cardiovascular disease, and bacterial infections [87]. For the treatment of those diseases, single-cell studies would be valuable in optimizing the treatment's efficacy [88,89]. While comparable to apoptosis, autophagy is engaged to intricate signaling pathways even to cell survival.…”
Section: Histone Modification In Cancer and Future Perspectivesmentioning
confidence: 99%